2017
DOI: 10.18697/ajfand.80.16965
|View full text |Cite
|
Sign up to set email alerts
|

Physico-chemical characteristics and fatty acid profile of Baillonella toxisperma pierre traditionally extracted edible oil from Cameroon forests

Abstract: Baillonella toxisperma Pierre oil is an edible oil obtained from the seeds of wildly growing timber producing B. toxisperma tree species in Cameroon and the rest of the Congo Basin forests of West and Central Africa. This oil can be an important source of fat that can be used as a source of food to humans and/or a source of raw materials in the cosmetics, pharmaceutical and nutraceutical industries, to produce important commercial products. In the present study, samples of the seeds of B. toxisperma were harve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…The main fatty acids of Baillonella toxisperma oils are oleic, stearic, and palmitic acids. The fact that the biochemical characteristics and fatty acid profile are comparable to common vegetable oils shows that the B. toxisperma oil is a potential source of valuable oil which might be used for edible, cosmetic, pharmaceutical and other industrial applications [ 71 ]. Etong and Mustapha [ 72 ] found that the oil of the bush mango Irvingia gabonensis contains six major fatty acids.…”
Section: Discussionmentioning
confidence: 99%
“…The main fatty acids of Baillonella toxisperma oils are oleic, stearic, and palmitic acids. The fact that the biochemical characteristics and fatty acid profile are comparable to common vegetable oils shows that the B. toxisperma oil is a potential source of valuable oil which might be used for edible, cosmetic, pharmaceutical and other industrial applications [ 71 ]. Etong and Mustapha [ 72 ] found that the oil of the bush mango Irvingia gabonensis contains six major fatty acids.…”
Section: Discussionmentioning
confidence: 99%
“…The main fatty acids of Baillonella toxisperma oils are oleic, stearic and palmitic acids. The fact that the biochemical characteristics and fatty acid pro le are comparable to common vegetable oils shows that the B. toxisperma oil is a potential source of valuable oil which might be used for edible, cosmetic, pharmaceutical and other industrial applications [96]. Etong and Mustapha [97] found that the oil of the bush mango Irvingia gabonensis contains six major fatty acids.…”
Section: Discussionmentioning
confidence: 99%
“…The main fatty acids of Baillonella toxisperma oils are oleic, stearic and palmitic acids. The fact that the biochemical characteristics and fatty acid pro le are comparable to common vegetable oils shows that the B. toxisperma oil is a potential source of valuable oil which might be used for edible, cosmetic, pharmaceutical and other industrial applications [65]. Etong and Mustapha [66] found that the oil of the bush mango Irvingia gabonensis contains six major fatty acids.…”
Section: Discussionmentioning
confidence: 99%